HUBUNGAN KOORDINASI DAN KELINCAHAN TERHADAP RESIKO CEDERA PEMAIN FUTSAL DI SMP MUHAMMADIYAH CILEGON - Meiza Anniza; Dadi Iskandar (Poltekkes 'Aisyiyah Banten, 2022)
Background: Sports injuries are all forms of abnormalities and damage that occur in the body both in body structure and function that cause pain, caused by physical movement activities and sports and occur directly or indirectly. Objective: To determine the relationship between coordination and agility to the risk of injury to futsal players at SMP Muhammadiyah Cilegon. Methods: This study used a descriptive correlational method with total sampling technique. The sample in this study was futsal players aged 12 to 15 years at the Muallimin Muhammadiyah Yogyakarta Madrasah, totaling 52 students. Results: Kendall's tau test results obtained agility p = 0.012 which has a value smaller than (p = 0.05) so it can be said that there is a relationship between agility and the risk of injury. While the Kendall's tau test obtained coordination p = 0.329 which has a value greater than (p = 0.05) so it can be said that there is no relationship between coordination and risk of injury. Conclusion: It can be concluded that there is a relationship between agility and the risk of injury to futsal players in Madrasahs. Muallimin Muhammadiyah Yogyakarta and there is no relationship between coordination and the risk of injury to futsal players at SMP Muhammadiyah Cilegon. Suggestion: It is recommended to conduct a study on other factors that influence these results, adding more samples and changing the measuring instrument used by the current researcher, in order to get better results.